(untitled) - Walker, Beth V (New York, 2003)
An Employee's Guide to Stock Options provides the first comprehensiveand comprehensibleguide to employee stock options, covering what they are, what they are worth, how to maximize their value, and more.
Keywords: Employee stock options,Stock options